GUİNEA PİG'LERDE TOPİKAL E VİTAMİNİNİN ULTRAVİYOLE B'YE KARŞI KORUYUCU ETKİSİ VE SERBEST RADİKALLERİN ÖNEMİ - UYAR, BELKIZ (Fırat Üniveristesi, 1998)
Çalışmamızda bir antioksidan ajan olan E vitamini asetat'ın, tek doz ultraviyole B (UVB) radyasyonundan önce ve sonra topikal olarak uygulandığında UVB'ye bağlı olarak gelişen antioksidan kapasitede ki bozulmayı ne ölçüde değiştireceğini deneysel olarak araştırmayı amaçladık. Çalışmamızı 56 albino kobay (guinea pig) ile yaptık. Anestezi uygulanan kobayların sırt bölgeleri ortalama 35 cm2 olacak şekilde tıraşlandı. Daha sonra kobaylar dört gruba ayrıldı. Kontrol grubuna traştan sonra hiç bir işlem uygulanmadı. Bir grup kobaya yalnızca UVB verildi. Bir kısmına UVB verildikten hemen sonra tek doz topikal olarak E vitamini asetat uygulandı. Bir kısmına ise önce 3 hafta süre ile topikal E vitamini asetat uygulayıp, en son uygulanan topikal E vitamini asetattan sonra UVB verildi. Kontrol grubu hariç diğer gruplardaki kobaylardan yarısı UVB verildikten 24 saat sonra, kalan yarısı 48 saat sonra dekapitasyonla öldürüldü. Dekapite edilen tüm kobayların deri, karaciğer, plazma, eritrositlerinde lipit peroksit, hemoglobin ve deride süperoksit dismutaz, Deri ve eritrositlerde glutatyon peroksidaz, eritrositlerde redükte glutatyon çalışıldı. Topikal E vitamini uygulanan her iki grupta da deri ve karaciğer lipid peroksit değerleri sadece UVB uygulanan grupta ki artışa göre anlamlı derecede baskılandı. Eritrosit lipid peroksit değerleri topikal E vitamini asetad uyguladığımız her iki grupta da yalnızca UVB uygulanan grup ile parelellik gösterdi. Kontrol grubuna göre 48. Saatte artan plazma lipid peroksit seviyeleri ise E vitamini uygulanan her iki grupta da yalnızca UVB uygulanan gruba göre daha fazla bir artış gösterdi. Deri GSHPx seviyesinde yalnızca UVB uygulanan gruba göre 24. saatte olan azalmanın, E vitamini uygulanan her iki grupta da 48. saatte daha az bir artış gösterdiği kaydedildi. Fakat bunlar istatistiksel olarak anlamlı değildi. Eritrosit GSHPx değerleri 48.saatte sadece UVB uygulanan gruba göre tek doz E vitamini uygulanan grupta istatistiksel olarak anlamlı olmayan, 3 hafta e vitamini uygulanan grupta ise istatistiksel olarak anlamlı olan belirgin bir azalma gözlendi. Çalışmamızda sadece UVB verilen ve E vitamini asetat uygulanan her iki grup eritrosit GSH değerleri kontrol gurubuna göre istatistiksel olarak anlamlı olacak şekilde yüksek bulundu. Kontrol grubu hariç diğer gruplar arasında istatistiksel olarak anlamlı bir fark yoktu. UVB uygulamasıyla azalan deri v hemoglobin SOD değerleri tek doz E vitamini asetat uygulanan grupta 3 hafta E vitamini uygulanan gruba göre daha iyi bir düzelme sağlamıştır. UVB radyasyonundan sonra tek doz E vitamini asetat uygulamasının ve UVB radyasyonundan 3 hafta önce uygulanan E vitamini astat'ın UVB radyasyonunun zararlı etkilerine karşı faydalı olduğu sonucuna vardık.

In this study, it is aimed to experimentally investigate how much the topical application of vitamin E acetate, an antioxidant agent, changes the deterioration of antioxidant capacity due to ultraviolet B (UVB) radiation, before and after single dose UVB radiation. 56 albino guinea pigs were taken to the study. Back area of the anesthetized guinea pigs were shaved with an average of 35 cm2 The guinea pigs were divided into four groups. Nothing was applied to the control group after shaving. One group of guinea pigs were only given UVB. One dose of vitamin E acetate was administered topically to another group immediately after they were given UVB. Vitamin E acetate was applied topically to another group for 3 weeks, and after the last application of vitamin E, UVB was given. Excluding the control group, half of the guinea pigs in the groups were killed by decapitation 24 hours after the UVB exposure, and the other half were killed by decapitation 48 hours after the UVB exposure. All of the decapitated guinea pigs were studied for lipid peroxide in skin, liver, plasma and erythrocytes; for superoxide dismutase in haemoglobin and skin; for glutathione peroxidase in skin and erythrocytes, and for reduced glutathione in erythrocytes. In both groups with topically applied vitamin E, the skin and liver peroxide values were significantly suppressed compared to the increased levels of the group with only the UVB applied. In both groups with topically applied vitamin E, the erythrocyte lipid peroxide levels were comparable with the levels of the group with only the UVB applied. The increase of the plasma lipid peroxide levels measured at the 48th hour after the application of the UVB compared to the control groups were higher in the groups that are treated with vitamin E acetate compared to the group treated with only the UVB. It was noted that the decrease in skin GSHPx level at 24th hour compared to the group treated with UVB only showed a less increase at 48th hour in both groups treated with vitamin E, however, these were not statistically significant. Decreases of erythrocyte GSHPx values at 48th hour were statistically not significant in the single dose E vitamin group compared to the only UVB treated group and a statistically significant decrease was observed in the 3 weeks E Vitamin treated group compared to the only UVB treated group. In all the groups, the skin GSHPx levels were decreased compared to the control group. These levels were higher at the 48th hour after the UVB application compared to the levels at the 24th hour. The difference between the levels at the 48th hour and at the 24th hour was less in the groups treated with vitamin E acetate; in fact, this difference was statistically insignificant in the groups treated with vitamin E acetate. In all three groups the erythrocyte GSHPx levels at the 48th hour after the UVB application were decreased compared to the control group. The difference between the GSHPx levels of the group with only the UVB treatment and the group treated with single dose vitamin E acetate was statistically insignificant. The difference between the GSHPx levels of the group with only the UVB treatment and the group treated with vitamin E acetate for three weeks was statistically significant. In the study, erythrocyte GSH values of the group with only UVB treated and both groups with vitamin E acetate were found to be increased statistically significantly compared to the control group. The differences between the groups, excluding the control group, were statistically insignificant. The group treated with single dose of vitamin E acetate demonstrated better recovery from the decreased skin and haemoglobin SOD values resulted from the UVB application, compared to the group treated with 3 weeks of vitamin E. It is concluded that the application of the single dose of vitamin E acetate after the UVB radiation and the administration of vitamin E acetate 3 weeks before the UVB radiation were effective against the harmful effects of the UVB radiation.
Protective effects of vitamin e on uvb irradiation in guinea pigs: importance of free radicals
Keywords: Dermatoloji; Dermatology